First Report of a Toxic Nodularia spumigena (Nostocales/ Cyanobacteria) Bloom in Sub-Tropical Australia. I. Phycological and Public Health Investigations - McGregor, Glenn B. (MDPI, 2012)
Cyanobacterial blooms represent one of the most conspicuous and widespread waterborne microbial hazards to human and ecosystem health. Investigation of a cyanobacterial bloom in a shallow brackish water recreational cable ski lake in south-eastern Queensland, Australia revealed the dominance of the toxigenic species Nodularia spumigena. The bloom spanned three months, during which time cell concentrations exceeded human guideline thresholds for recreational risk, and concentrations of the hepatotoxic cyanotoxin nodularin exceeded 200 µg L(−1). Cyanotoxin origin and identification was confirmed by amplification of the ndaF-specific PCR product and sequencing of the 16S rRNA gene. From the limited data available leading up to, and throughout the bloom, it was not possible to establish the set of causative factors responsible for its occurrence. However a combination of factors including salinity, hydraulic retention time and nutrient status associated with an extended period of drought are likely to have contributed. This was the first known occurrence of this species in bloom proportions from sub-tropical Australia and as such represents a hitherto uncharacterized risk to human and ecosystem health. It highlights the need for adaptive monitoring regimes to ensure a comprehensive understanding of the potentially toxic cyanobacteria likely to inhabit any given region. Such monitoring needs to recognize that cyanobacteria have a significant capacity for range expansion that has been facilitated by recent changes in global climate.